On Adaptation of Names of Greek Origin in the Serbian Language (On the Corpus Excerpted from the Materials from the 14th to 21st Century) - Rakić Mladenović, Jugoslava G (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper examines the adaptation of names of Greek origin in the Serbian language. Names taken from the Greek language, passing from one language to another, had to go through a certain type of adaptation. Adaptation of names took place in different ways, first of all by adapting to all the phonetic laws of the language they enter and by adapting to its grammatical structure. The analysis was done on a corpus extracted from historical monuments and from statistical data of the Republic Institute of Statistics until 2012 (for the period from 1940 and earlier until 2011), from which a selection of the most frequent Greek and Greekized names in the Serbian language was made out of 14th to the 21st century. Characteristic phenomena in the process of adaptation of names of Greek origin and those that entered the Old Slavic language through Greek were analyzed from the phonetic and morphological aspects with adequate examples of names in which these phenomena occur. The adaptation of the name is presented through the forms given first in the Old Slavic language, which were then transmitted in the same form or further adapted in editorial literacy-in the Serbo-Slavic language (post-Lere Sava norm) and finally in the modern Serbian language. In the tabular representation, the forms of the names in the Greek language are also given in order to gain a better insight into the adaptation process.
Keywords: anthroponymy; adaptation; Greek names and Greekisms; monuments